2018
DOI: 10.1142/s0219498818501153
|View full text |Cite
|
Sign up to set email alerts
|

Primitivity of PRESENT and other lightweight ciphers

Abstract: We provide two sufficient conditions to guarantee that the round functions of a translation based cipher generate a primitive group. Furthermore, under the same hypotheses, and assuming that a round of the cipher is strongly proper and consists of m-bit S-Boxes, with m = 3, 4 or 5, we prove that such a group is the alternating group. As an immediate consequence, we deduce that the round functions of some lightweight translation based ciphers, such as the PRESENT cipher, generate the alternating group.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Later, a similar methodology called invariant subspace attack has been introduced for the cryptanalysis of PRINTcipher [20]. Today, the resistance to the imprimitivity attack of many known constructions has been proved [1,2,10,25,26], and primitivity conditions have been established also for large families of ciphers. For example, Aragona et al [3,Theorem 4.5] have shown that the primitivity of the group generated by the rounds of an FN can be reduced to the primitivity of the group generated by the rounds of an SPN whose round functions are the ones implemented as F-functions 1 One remarkable exception is a paper due to Wernsdorf [28] which shows that the multiplyaddition box at the center of the round of IDEA generates the alternating group on F 32 2 and where it is conjectured that also the entire rounds of IDEA generate the alternating group.…”
Section: Introductionmentioning
confidence: 99%
“…Later, a similar methodology called invariant subspace attack has been introduced for the cryptanalysis of PRINTcipher [20]. Today, the resistance to the imprimitivity attack of many known constructions has been proved [1,2,10,25,26], and primitivity conditions have been established also for large families of ciphers. For example, Aragona et al [3,Theorem 4.5] have shown that the primitivity of the group generated by the rounds of an FN can be reduced to the primitivity of the group generated by the rounds of an SPN whose round functions are the ones implemented as F-functions 1 One remarkable exception is a paper due to Wernsdorf [28] which shows that the multiplyaddition box at the center of the round of IDEA generates the alternating group on F 32 2 and where it is conjectured that also the entire rounds of IDEA generate the alternating group.…”
Section: Introductionmentioning
confidence: 99%
“…More relevant in [28], Paterson built a DES-like cipher, resistant to both linear and differential cryptanalysis, whose encryption functions generate an imprimitive group and showed how the knowledge of this trapdoor can be turned into an efficient attack to the cipher. For this reason, a branch of research in Symmetric Cryptography is focused on showing that the group generated by the encryption functions of a given cipher is primitive and not of affine type (see [4,5,6,11,17,18,31,33,34,35]). In this sense, our purpose is to give sufficient conditions for the primitivity of the group generated by the round functions of a wave cipher.…”
Section: Introductionmentioning
confidence: 99%
“…More relevant, in [23] Paterson built a DES-like cipher whose encryption functions generate an imprimitive group and showed how the knowledge of this trapdoor can be turned into an efficient attack to the cipher. For this reason, a branch of research in symmetric cryptography is focused on showing that the group generated by the encryption functions of a given cipher is primitive (see [3,4,5,9,12,13,25,28,29,30]).…”
Section: Introductionmentioning
confidence: 99%